Microbiology of Lebanon Bologna - Smith, James L. (1973)
Various aspects of the microbiology of the Lebanon bologna process were studied. Manufacture of Lebanon bologna appeared to be similar to that of summer sausage and other fermented sausages and consisted of a lactic acid fermentation by lactobacilli accompanied by the production of cured meat color from the reduction of nitrate by micrococci. The traditional process consists of aging coarse ground beef at 5 C for several days. Aging the beef for about 10 days was necessary to allow development of lactic acid bacteria; for successful fermentation, the concentration of lactic acid producers must be 10(4)/g or more. At least 3% NaCl was necessary to suppress the development of pseudomonads during the aging period; higher concentrations of salt suppress the development of the lactic acid-producing flora. During aging, in the presence of salt, the predominant flora developing on the meat consisted of catalase-positive, gram-positive rods and cocci; during fermentation at 35 C, the predominant flora became catalase-negative, gram-positive rods with characteristics of lactobacilli. Lebanon bologna could be made from frozen beef if the meat was thawed, salted, and aged. However, bolognas could not be made from unaged beef unless a lactic acid starter culture was used. The microflora of several commercial bolognas is reported also.